Neutrophil-to-Lymphocyte Ratio: A Biomarker to Monitor the Immune Status of Astronauts - Paul, Amber M.; Mhatre, Siddhita D.; Cekanaviciute, Egle; Schreurs, Ann-Sofie; Tahimic, Candice G. T.; Globus, Ruth K.; Anand, Sulekha; Crucian, Brian E.; Bhattacharya, Sharmila (Frontiers in Immunology, 2020)
A comprehensive understanding of spaceflight factors involved in immune dysfunction and the evaluation of biomarkers to assess in-flight astronaut health are essential goals for NASA. An elevated neutrophil to lymphocyte ratio (NLR) is a potential biomarker candidate, as leukocyte differentials are altered during spaceflight. In the reduced gravity environment of space, rodents and astronauts displayed elevated NLR and granulocyte to lymphocyte ratios (GLR), respectively. To simulate microgravity using two well-established ground-based models, we cultured human whole blood-leukocytes in high-aspect rotating wall vessels (HARV-RWV) and used hindlimb unloaded (HU) mice. Both HARV-RWV simulation of leukocytes and HU-exposed mice showed elevated NLR profiles comparable to spaceflight exposed samples. To assess mechanisms involved, we found the simulated microgravity HARV-RWV model resulted in an imbalance of redox processes and activation of myeloperoxidase-producing inflammatory neutrophils, while antioxidant treatment reversed these effects. In the simulated microgravity HU model, mitochondrial catalase-transgenic mice that have reduced oxidative stress responses, showed reduced neutrophil counts, NLR, and a dampened release of selective inflammatory cytokines compared to wildtype HU mice. Suggesting simulated microgravity induced oxidative stress responses that triggered inflammation. In brief, both spaceflight and simulated microgravity models caused elevated NLR, indicating this as a potential biomarker for future in-flight immune health monitoring.